Volume 5: 6th International Conference on Multibody Systems, Nonlinear Dynamics, and Control, Parts A, B, and C 2007
DOI: 10.1115/detc2007-34905
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Prediction of Great Salt Lake Elevation Time Series Based on ARFIMA

Abstract: The elevation of Great Salt Lake (GSL) has a great impact on the people of Utah. The flood of GSL in 1982 has caused a loss of millions of dollars. Therefore, it is very important to predict the GSL levels as precisely as possible. This paper points out the reason why conventional methods failed to describe adequately the rise and fall of the GSL levels — the long-range dependence (LRD) property. The LRD of GSL elevation time series is characterized by some most commonly used Hurst parameter estimation methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Compared to conventional integer order models, the AR-FIMA model gives a better fit and result when dealing with the data which possess the LRD property. Sun et al applied the ARFIMA model to analyze the data and predict the future levels of the elevation of Great Salt Lake (GSL) [3]. The results showed that the prediction results have a better performance compared to the conventional ARMA models.…”
Section: Detc2017-67483mentioning
confidence: 99%
“…Compared to conventional integer order models, the AR-FIMA model gives a better fit and result when dealing with the data which possess the LRD property. Sun et al applied the ARFIMA model to analyze the data and predict the future levels of the elevation of Great Salt Lake (GSL) [3]. The results showed that the prediction results have a better performance compared to the conventional ARMA models.…”
Section: Detc2017-67483mentioning
confidence: 99%
“…In the [73], the author highlights the necessity of long-memory models characterized also by a strong flexibility in modeling the low-lags autocorrelations by introducing ARFIMA models which represented a potentially powerful tool for modeling stationary hydrological records. Sun et al applied the ARFIMA model to analyze the data and predict the future levels of the elevation of Great Salt Lake (GSL) [74]. The results showed that the prediction results have a better performance compared to the conventional ARMA models.…”
Section: Solar Energymentioning
confidence: 99%
“…Compared to the conventional integer order models, the ARFIMA model gives a better fit and result when dealing with the data which possess the LRD property. Sun et al applied the ARFIMA model to analyze the data and predict the future levels of the elevation of Great Salt Lake (GSL) [7]. The results showed that the prediction results have a better performance compared to the conventional ARMA models.…”
Section: Introductionmentioning
confidence: 99%